Feasibility of Abdominal Magnetic Resonance Imaging in Patients With Residual Concentrated Enteric Contrast After Fluoroscopic Abdominal Examination. Issue 5 (18th September 2021) - Dane, Bari; Hindman, Nicole
Abstract : Objective: This study aimed to evaluate the image quality, image artifacts, radiologist confidence, and ability to provide definitive diagnosis for all patients with magnetic resonance imaging (MRI) performed after an abdominal fluoroscopic examination and to determine the utility of MRI in this setting. Methods: Thirty-one MRI examinations performed a median of 2 days after fluoroscopic bowel evaluation (barium, n = 13; iodine, n = 18), 20 within 3 days of MRI, were retrospectively reviewed. The image quality, artifact emanating from bowel, inhomogeneity artifact, radiologist confidence, ability to render a definitive diagnosis, and identification of emergent or important findings for all MRI examinations were assessed. These same features were evaluated on 5 computed tomographies performed after fluoroscopy (before the MRI) in the same cohort. Results: All 31 MRI examinations performed after fluoroscopic studies with concentrated barium or iodine solutions were diagnostic for answering the clinical question according to radiologist and report review, regardless of magnet strength and type of fluoroscopic contrast ingested. Magnetic resonance imaging after fluoroscopy had excellent overall image quality (mean score, 4.74/5), minimal to no artifact emanating from bowel (mean, 4.63/5), minimal inhomogeneity artifact (mean, 4.38/5), and excellent diagnostic confidence (mean, 4.98/5). No additional imaging was necessary for diagnosis after MRI. Computed tomography after fluoroscopy had lower overall image quality, more image artifacts, and lower diagnostic confidence ( P < 0.05). Conclusions: Magnetic resonance imaging is a useful tool for evaluating patients with retained concentrated enteric contrast from recent fluoroscopic examinations. In the absence of contraindication, MRI should be considered in the evaluation of urgent clinical problems in patients who recently underwent a fluoroscopic bowel evaluation.